IMPLEMENTASI SIMULASI FISIKA DALAM PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KUANTITAS MISKONSEPSI SISWA PADA KONSEP ELASTISITAS - Jaziroh, Yustina (2014)
The result of preliminary study showed student's difficulty to understand physics concept because of misconception. That misconception caused by learning's implementation which not appropriate and media which not describe concept well. Implementation of physics simulation in cooperative learning type jigsaw could be a solution. The purpose of this study was knowing the quantity of misconception between students that followed cooperative learning type jigsaw with using physics simulation and without using physics simulation, and then knowing student's respon about physics simulation in jigsaw. The method used was quasi experiment with non-equivalent control group post-test only. This study sampel was students class XI science in one of the Senior High School in Bandung. The result showed percentage of student's misconception that followed jigsaw with using physics simulation and without using physics simulation continued was 10,33% (low misconception) and 37,58% (middle misconception). In addition, 83,08% students gave positive respon to implementation of physics simulation in cooperative learning type jigsaw.